Hitman Anders and the meaning of it all : a novel - Jonasson, Jonas, 1961- (Ecco, 2016)
"A brilliant satirical novel set in modern Sweden, a story of idealism and fanaticism, gangsters and entrepreneurs, sensationalism and spirituality, that explores the values that matter in contemporary life." --